Effects of role play activities on English speaking performance of students majoring in Tourism - Trương Mai Tuyết Trinh (Trường Đại học Trà Vinh, 2024)
The purpose of this study is to test the effects of applying role-play activities on English for Tourism students' speaking performance. Moreover, teachers can find out students' perceptions about the role-play activities in their speaking class.